Optimizing Infill Parameters for Improved Mechanical Performance and Cost Savings in Additive Manufacturing - ARIKAN, Volkan (International Journal of Computational and Experimental Science and Engineering, 2023)
In this study, compression tests were performed on the samples produced with PLA filament with different infill parameters and infill densities by additive manufacturing method and their mechanical performances & static energy absorption capabilities were evaluated. According to the results obtained, it was determined that the samples with triangular and tri-hexagonal infill parameters performed better and it has been shown that time, material and energy can be saved without losing materials mechanical performance.